Safety and efficacy of cannabidiol-cannabidiolic acid rich hemp extract in the treatment of refractory epileptic seizures in dogs - Garcia, Gabriel A.; Kube, Stephanie; Carrera-Justiz, Sheila; Tittle, David; Wakshlag, Joseph J. (Frontiers in Veterinary Science, 2022)
The use of cannabidiol (CBD) in childhood refractory seizures has become a common therapeutic approach for specific seizure disorders in human medicine. Similarly, there is an interest in using CBD, cannabidiolic acid (CBDA) or cannabinoid-rich hemp products in the treatment of idiopathic epilepsy in dogs. We aimed to examine a small cohort in a pilot investigation using a CBD and CBDA-rich hemp product for the treatment of refractory epileptic seizures in dogs. Fourteen dogs were examined in a 24-week randomized cross-over study being provided placebo or CBD/CBDA-rich hemp extract treatment at 2 mg/kg orally every 12 hours for each 12-week arm of the study. Serum chemistry, complete blood counts, serum anti-seizure medication (ASM) concentrations and epileptic seizure frequency were followed over both arms of the cross-over trial. Results demonstrated that besides a mild increase in alkaline phosphatase, there were no alterations observed on routine bloodwork at 2, 6 and 12 weeks during either arm of the study. Epileptic seizure frequency decreased across the population from a mean of 8.0 + 4.8 during placebo treatment to 5.0 + 3.6 with CBD/CBDA-rich hemp extract (P = 0.02). In addition, epileptic seizure event days over the 12 weeks of CBD/CBDA-rich hemp treatment were 4.1 + 3.4, which was significantly different than during the 12 weeks of placebo treatment (5.8 + 3.1; P =0.02). The number of dogs with a 50% reduction in epileptic activity while on treatment were 6/14, whereas 0/14 had reductions of 50% or greater while on the placebo (P = 0.02). No differences were observed in serum zonisamide, phenobarbital or bromide concentrations while on the treatment across groups. Adverse events were minimal, but included somnolence (3/14) and transient increases in ataxia (4/14) during CBD/CBDA-rich hemp extract treatment; this was not significantly different from placebo. This further indicates that providing CBD/CBDA-rich hemp extract during refractory epilepsy (only partially responsive to ASM), in conjunction with other ASM appears safe. Based on this information, the use of 2 mg/kg every 12 hours of a CBD/CBDA-rich hemp extract can have benefits in reducing the incidence of epileptic seizures, when used concurrently with other ASMs.